Website www.goal.com as an Instructional Model Development - Mariska Febrianti; Azizatul Banat; Arifto Juniardi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Generally someone who is said to master English or at least who can communicate is the one who masters in 4 basic skills, namely listening, speaking, reading and writing. While the problems that researchers often encounter in the field are still far beyond the basic things, namely the lack of vocabulary mastery by sports students at Dehasen University, Bengkulu. Therefore, through this study, the researchers intended to motivate sports students to learn English by developing instructional models that suitable to their characteristics. Researchers believe that utilizing this student’s love for sports can arouse their enthusiasm in learning so that researchers utilize the website www.goal.com and collaborate with sports lecturers and English lecturer to develop instructional models in the form of existing English teaching materials which are then modified in accordance to characteristics of sports students. The method used in this study is R D (Research Development). The results of this study are the existence of instructional model using the website www.goal.com can increases the vocabulary mastery of sports students and they are become more motivated in learning in the classroom. It can be seen from the average value of the pre-test and post-test. Keywords: development of instructional models, sports students.